2018
DOI: 10.21475/ajcs.18.12.05.pne1201
|View full text |Cite
|
Sign up to set email alerts
|

First insights of soybean stem fly (SSF) Melanagromyza sojae control in South America

Abstract: The occurrence, distribution, and intensity of damages caused by Melanagromyza sojae on soybean fields in Brazil and Paraguay indicate the need of information regarding the effect of insecticides and mode of applications to its control. The aim of this study was to evaluate insecticide applications at soybean sowing and during the early soybean stages to control M. sojae. Two experiments were carried. In the 1 st experiment, 12 insecticides were applied at sowing as a seed treatment (ST) or in the sowing furro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 7 publications
(9 reference statements)
0
9
0
Order By: Relevance
“…Talekar, 1990;Van den Berg, 1998) as well as insecticides applied via seed or foliar sprays (e.g. Adak, 2012;Jadhav et al, 2013;Curioletti et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Talekar, 1990;Van den Berg, 1998) as well as insecticides applied via seed or foliar sprays (e.g. Adak, 2012;Jadhav et al, 2013;Curioletti et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Adak 2012, Jadhav et al 2013) has also been reported. Curioletti et al (2018) recommended spraying Chlorantraniliprole as seed treatment, followed by foliar spraying of Chlorpyrifos until 10 days after plant emergence, and repeated once in an interval shorter than 10 days. On the other hand, control strategies for M. sojae in South America remain scarce and poorly tested.…”
Section: Management Strategiesmentioning
confidence: 99%
“…While some studies have proposed chemical (e.g. Curioletti et al 2018) and biological (e.g. Beche et al 2018) strategies for M. sojae management, control efficiency is often impaired by the concealed feeding habit of the larvae.…”
Section: Introductionmentioning
confidence: 99%
“…To control the soybean stem fly infestation, crop rotation, adequate soil preparation and avoidance of late planting are the most effective control practices (Hirose & Moscardi 2012). Research on the management of this insect with insecticides is also under development (Curioletti et al 2018).…”
Section: Research Notementioning
confidence: 99%